Adverse Events of Massage Therapy in Pain-Related Conditions: A Systematic Review. (12th August 2014) - Yin, Ping; Gao, Ningyang; Wu, Junyi; Litscher, Gerhard; Xu, Shifen
Abstract : Pain-related massage, important in traditional Eastern medicine, is increasingly used in the Western world. So the widening acceptance demands continual safety assessment. This review is an evaluation of the frequency and severity of adverse events (AEs) reported mainly for pain-related massage between 2003 and 2013. Relevant all-languages reports in 6 databases were identified and assessed by two coauthors. During the 11-year period, 40 reports of 138 AEs were associated with massage. Author, year of publication, country of occurrence, participant related (age, sex) or number of patients affected, the details of manual therapy, and clinician type were extracted. Disc herniation, soft tissue trauma, neurologic compromise, spinal cord injury, dissection of the vertebral arteries, and others were the main complications of massage. Spinal manipulation in massage has repeatedly been associated with serious AEs especially. Clearly, massage therapies are not totally devoid of risks. But the incidence of such events is low.